Emptiness and fastidiousness in Christian Krachtʼs Faserland - Bonomo, Daniel R. (Pandaemonium Germanicum, 2014)
If not one of the best, Christian Kracht is certainly one of the most talked about authors of fiction in the German language nowadays. His carreer goes back to 1995, when his first novel Faserland was published ‒ an event which helped to shape the so called Popliteratur. However, whether it is the zero hour of a work composed of other good moments or whether it is the literary mark of a generation, Faserland is not only an example of a pop reality. It has also deserved frequent reading and interpretations, reprints and critical approaches, attracting by these means the attention of literary historiography. The novel narrates a few days' wanderings of a narcotized and affluent young man from Northern to Southern Germany reaching as far as Switzerland. There is no great adventure in the story, but the book leaves rather an impression of emptiness and fastidiousness which accompanies a senseless life. In this text, I investigate the kind of boredom produced by Faserland.